2017
DOI: 10.1016/j.foodres.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Current research, regulation, risk, analytical methods and monitoring results for nicarbazin in chicken meat: A perspective review

Abstract: This review presents up-to-date information about current research on nicarbazin, one of the most used anticoccidials in poultry production. The focus is to elucidate regulation concerning nicarbazin, limits for its residues in food, how maximum residue limits in different countries are calculated regarding edible chicken tissues and the possible implications in human health. Analytical methods to extract and quantify this residue, expressed as dinitrocarbanilide (DNC) are presented and discussed, including qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Similar conclusions have been reported by Dorne et al [25] who reported that no appreciable risk for consumers could be identified for LAS, MAD, MON, NAR, NIC, SAL, DEC, DIC and ROB following the consumption of meat, offal or eggs derived from non-target animals. Another study developed by Bacila et al [7] reports that the consumption of usual daily quantities of poultry products, considering the ADIs, is unlikely to pose any risk to human health related to NIC, one of the most used anticoccidials in poultry production. These considerations on health risk posed by coccidiostatic residues also were corroborated by Kadykalo et al [5] who analyzed several aspects of the problem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar conclusions have been reported by Dorne et al [25] who reported that no appreciable risk for consumers could be identified for LAS, MAD, MON, NAR, NIC, SAL, DEC, DIC and ROB following the consumption of meat, offal or eggs derived from non-target animals. Another study developed by Bacila et al [7] reports that the consumption of usual daily quantities of poultry products, considering the ADIs, is unlikely to pose any risk to human health related to NIC, one of the most used anticoccidials in poultry production. These considerations on health risk posed by coccidiostatic residues also were corroborated by Kadykalo et al [5] who analyzed several aspects of the problem.…”
Section: Resultsmentioning
confidence: 99%
“…Coccidiostats are pharmacologically active molecules employed, since 1940, to prevent and inhibit parasitic protozoa of the genus Eimeria , referred to as coccidia, causing a very contagious disease of the gastrointestinal tract in many farmed animals [1,2]. Coccidiosis represents a major disease in poultry, causing intestinal lesions, scarce weight gain, poor feed conversion and poor egg production; in its acute form, coccidiosis causes high mortality rates [3,4,5,6,7]. Aside from intensively farmed animals, such as poultry, coccidiosis also affects extensively reared species including sheep, cattle, pigs and rabbits [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, paper [14] reported exacerbation of certain conditions of ischemic disease by residues of coccidiostats in food. Although there are cases of acute toxicity, special attention should be paid to the chronic toxicity resulting from the prolonged exposure to low levels of coccidiostats [24].…”
Section: Introductionmentioning
confidence: 99%
“…The apparent reason for this massive issue is the excessive addition of prophylactic drugs as a feed additive for fattening the chickens in a shorter period. In recent times, few articles reported about the effects of nicarbazin ; among the reports, few states that nicarbazin can act as a reproduction inhibitor and it also decreases the hatchability of eggs . Therefore, constructing a cheap , effective and sensitive device for the real‐time detection and quantification of NCZ creates great interest among the researchers.…”
Section: Introductionmentioning
confidence: 99%